Organ Preservation Strategies in Laryngeal Chondrosarcoma. (21st August 2021) - Rüller, Karina; Sittel, Christian; Kölmel, Jan‐Constantin; Burghartz, Marc; Steimer, Johannes; Fiz, Francesco; Piazza, Cesare; Peretti, Giorgio; Fiz, Ivana
Abstract : Objectives/Hypothesis: Laryngeal chondrosarcoma (LC) is a rare, slowly growing malignancy. The preferred treatment is laryngeal preservation surgery (LPS). Some patients may require multiple interventions or total laryngectomy (TL). We investigated risk factors for retreatment and TL, and assessed the impact of LPS on oncological and functional outcomes. Study Design: Case series Methods: We searched our institution database for LC. Tumor grading, localization, and margin status were tested as predictors of recurrence and organ preservation. Results: We included 21 patients (seven females, mean age 58 ± 12 years). LPS was applied in 20 (95.2%) of them as a primary procedure. Six patients were treated by transoral approach and 14 received "open‐neck" LPS. Fifteen (71.4%) were operated only once, while six patients underwent a total of 15 adjunctive procedures. Additional operations were always performed for recurrence of tumors localized within the cricoid plate. The histological grading was G1 in 81% and G2 in 19%. However, two patients with a primary G1 LC showed a G2 recurrence. Reoperations for recurrence were more frequent among patients with G2 in respect to G1 histology (83% vs. 7%, P  < .001). Fifty percent of G2 LC and 8% of G1 underwent TL ( P  < .05). Margin status had no influence on recurrence rate. Conclusions: Patients with G2 LC have more recurrences requiring surgery and a higher incidence of TL. Cricoid plate localization is relevant for organ preservation. Margin status signals possible disease persistence, without influencing the need for future surgeries. Need for reoperation entails a risk of not being able to maintain organ functionality. Level of Evidence: 4 Laryngoscope, 132:838–843, 2022